THE ADAPTABILITY OF NATIVE TO LAND ADMINISTRATION IN SARAWAK, MALAYSIA - Toh Ming Liang; Tan Liat Choon; Tan Wee Vern; Muhamad Uznir Ujang; Nor Suhaibah Azri; Thoo Ai Chin; Looi Kam Seng, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Sarawak, a home to natives which comprised more than two-third of the State’s total population. Driven by the multi-ethnic, multi-religious and multi-cultural nature of the natives, the land administration in Sarawak is facing enormous challenges to bridge the gaps between modern land administration systems and native customary tenure. The perception of native towards land governance is a crucial aspect in determining the success of the land administration system. In light of this, the study aims to explore the adaptability of the natives to the current practices of native land governance in Sarawak. Being quantitative in nature, the first step involves the utilisation of Chi-Square test of independence to examine the relationships between two categorical variables (age and measurement of adaptability). The second step is to quantify the level of adaptability by using descriptive analysis. Based on the quota sampling method from 512 respondents, 8 out of 10 Chi-square tests implied that the adaptability towards the current native land governance is affected by the age of the natives; a trend which younger adults are more agreeable to the current native land governance compared to the groups with older age. However, results indicate that the overall rate of acceptance is still far from satisfaction, especially in terms of the issuance of native titles. Based on the findings, the paper ends with the recommendations to improve the native land governance in Sarawak.